Liver Diseases and Long Non-Coding RNAs: New Insight and Perspective - Quagliata, Luca; Terracciano, Luigi M. (Frontiers in Medicine, 2014)
The new landscape of human transcriptome along with the identification of numerous long non-coding RNAs (lncRNAs) has dramatically altered our approach to study diseases. It is now imperative to decipher the biological functions of these transcripts and how they impact on human cell and pathophysiology. Nonetheless, already at this very early stage of their study, the involvement of lncRNAs in cell transformation is emerging as a key aspect. Recently, researchers have started to explore the implications of lncRNAs alteration in hepatic pathophysiology. In this review we will discuss in details several examples of liver-disease relevant lncRNAs. Many lncRNAs have been shown to play a major role in Hepatocellular carcinoma (HCC). For such type of tumour with an increasing incidence and a high mortality rate, it is crucial to identify new therapeutic targets and biomarkers to predict response to therapy. LncRNAs present as a promising new resource. One major challenge for the future would be to systematically address the lncRNAs expression among the different cellular components of the liver. To achieve this goal, a combination of clinically driven, genetically defined, morphologically classified and molecular-based studies will have to be performed. In conclusion, lncRNAs will undoubtedly provide a rewarding field of study and most importantly a new resource to identify new disease associated biomarkers and molecular targets for therapy for liver diseases.